Interpreting Yoknapatawpha reactions towards miscegenation in Faulkner’s light in august - Hanita Hanim, Ismail (2019)
Faulkner’s Light in August (1932) is set in the fictional Yoknapatawpha county– a town that witnesses the thrashing of a child who then turned into a young man, believing he is a mullato. By highlighting on other characters and their perception of this mulatto, this paper contends for its focus, which is not on Joe Christmas. Rather, this paper discusses over Faulkner’s representations of reactions towards miscegenation, as portrayed in interpretations provided by the Yoknapatawpha community in Light. The use of Husserlian Phenomenological Analysis is employed in deciphering Faulkner’s representations of the Yoknapatawpha who are observed among characters like Doc Hines, Simon McEachern and Percy Grimm who refuse to condone threats towards racial purity. Evidences are carefully selected from the text in order to avoid Intentional Fallacy in proving interpretations against miscegenation. In conclusion, there are ranges of reactions observed; the community either abrasively rejects miscegenation (like Doc Hines and Percy Grimm) or approach the situation in a diplomatic manner (like Simon McEachern). Other characters like Joanne Burden and the children at the orphanage are also looked into in order to derive at societal reactions towards Christmas as a subject of miscegenation. Either way, Faulkner’s representations of reactions validate a historical refusal to embrace miscegenation as part of the New America, which makes an interesting research on reception towards global changes, especially those occurring in the postmodern world.